Manajemen Strategik Kepala Madrasah dalam Mengimplementasikan Visi dan Misi untuk Pengembangan MI Ma’arif NU Miftahul Ulum Driyorejo - Aprilia Hidayat (PT. Nawa Edukasi Nusantara, 2025)
This study aims to analyze the strategic management applied by the principal of Madrasah Ibtidaiyah (MI) Ma’arif NU Miftahul Ulum in implementing the vision and mission for madrasah development. The research uses a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, documentation, and literature review of relevant sources. The results show that the principal plays an important role in formulating, implementing, evaluating, and implicating the vision and mission through a strategic management approach that involves all stakeholders. The implementation of the vision and mission is carried out through flagship programs such as religious habituation, academic development, and infrastructure improvement. Constraints faced are mainly related to funding and delays in fund allocation, but these can be overcome with participatory strategies and collaboration with the madrasah committee and the community. This study concludes that the principal's strategic management significantly influences the quality improvement and development of the madrasah.